Influence of xylan content on the oxygen delignification performance of eucalypt kraft pulps as studied using prehydrolysis and xylanase treatments - Helena Wedin; Stefan Antonsson; Martin Ragnar; Mikael E. Lindström (BioResources, 2012)
Common metrics for evaluating the efficiency of oxygen delignification include the kappa number and Klason lignin content. As a change in xylan content often leads to a change in HexA content, the kappa number must be corrected for the HexA contribution before evaluating the degree of oxygen delignification when trying to understand the process in detail. Questions could also be raised about the accuracy of the Klason lignin method for oxygen-delignified hardwood kraft pulps, since the amount of residual lignin is small in such pulp. This study investigates the influence of xylan content on oxygen delignification efficiency in Eucalyptus urograndis kraft pulps. Xylan content was varied using two methods: treatment with xylanase and with acid prehydrolysis for various times before kraft cooking. The degree of oxygen delignification, expressed as the HexA-corrected kappa number, indicated no significant trend with xylan removal, and no significant trend was evident when expressed as Klason lignin content.